Badan Hukum Yayasan dan Tata Kelola Yayasan di Indonesia: Analisis Yuridis terhadap Implementasi Prinsip Good Governance dalam Mewujudkan Akuntabilitas dan Kepastian Hukum - A.M Tasmika (Media Hukum Indonesia (MHI), 2026)
A foundation is a legal entity established to pursue social, religious, and humanitarian objectives through the separation of the founder's assets from those of the legal entity. This legal status grants the foundation the capacity to independently hold rights and obligations, engage in legal relationships, and bear responsibility for its actions through its governing organs established in accordance with applicable laws and regulations. In practice, however, foundation governance continues to face various challenges, including management disputes, misuse of assets, weak supervisory mechanisms, and the suboptimal implementation of good governance principles. This study aims to analyze the legal status of foundations as legal entities under Indonesian positive law and to examine the implementation of the principles of transparency, accountability, responsibility, independence, and fairness in foundation governance. The research employs a normative legal research method using statutory, conceptual, and case approaches. The findings indicate that Law Number 16 of 2001 concerning Foundations, as amended by Law Number 28 of 2004, provides an adequate legal framework for recognizing foundations as legal entities. Nevertheless, the effectiveness of this legal framework largely depends on the quality of organizational governance and the level of compliance of foundation organs with the principles of good governance.